Neighborhood characteristics and crime: a test of Sampson and Groves' model of social disorganization - Sun, Ivan Y. (Western criminology review, 2004)
In 1989 Sampson and Groves proposed a model of social disorganization. In this model, neighborhoods with low socioeconomic status, high residential mobility, racial heterogeneity, and family disruption were predicted to have sparse local friendship networks, low organizational participation, and unsupervised youth groups. These, in turn, were predicted to increase neighborhood crime rates. Although Sampson and Groves’ work represents the most complete model of social disorganization to date, it has only been tested twice and then on the same data set. Using data from 36 neighborhoods from 7 U.S. cities, this study examines extensions of Sampson and Groves’ model suggested by past research findings. The results indicate that Sampson and Groves’ model is modestly supported by the data. Social disorganization variables are more effective in transmitting the effects of neighborhood structural characteristics on assault than on robbery. Implications of the study and directions for future research are discussed.